Amnesty International as a Human Rights Actor: An analysis of Amnesty Internationals reproduction of its self-proclaimed identity and morality as a Human Rights Actor - Nejman,Filippa (2024)
From the rise of the 60s and 70s human rights focused advocacy and the founding of Amnesty International in 1961, that pioneered the concept of a global membership, Amnesty International (AI) is today one of the largest and most well-known human rights organisations in the World. Advocacy human rights focused international NGOs like Amnesty International often position themselves as: impartial and non-political human rights actors. Naturally these NGOs just like the concept of human rights have a high normative force. This thesis aims to examine AIs positioning of itself in relation to fundamental human rights concepts such as: universalism and impartiality and how these are communicated. Theories used are Habermas Communicative Action Theory and Stephen Hopgoods division of two types of human rights actors. The institutionalised and professionalised advocacy that follows from NGOization will also serve as a contextual background. The thesis also examines AIs anti-political stance, which includes their claim of impartiality, the notion of being part of a "Global Civil Society" and the narrative of standing with all victims.
Keywords: Amnesty International; human rights; human rights actor; human rights claims; human rights discourse NGOs; NGOization; moral authority; impartiality; positioning; normative force